Food subsidies in developing countries: costs, benefits, and policy options - Pinstrup-Andersen, Per (International Food Policy Research Institute, 1988)
Governments of most countries attempt to influence the price consumers pay for food. In low-income countries the aim is frequently one of reducing consumer food prices below a free-market level. The results are what in this book is called consumer-oriented food subsidies. The goals of subsidy programs and policies vary among countries and over time and may include desires to improve the real purchasing power of all or certain groups of consumers, to reduce or eliminate calorie and nutrient deficiencies in low-income population groups, to maintain low urban wages, to assure social and political stability, and a number of other goals.